The antioxidant master glutathione and periodontal health - Vivek Kumar Bains; Rhythm Bains (Dental Research Journal, 2015)
Glutathione, considered to be the master antioxidant (AO), is the most-important redox regulator that controls inflammatory processes, and thus damage to the periodontium. Periodontitis patients have reduced total AO capacity in whole saliva, and lower concentrations of reduced glutathione (GSH) in serum and gingival crevicular fluid, and periodontal therapy restores the redox balance. Therapeutic considerations for the adjunctive use of glutathione in management of periodontitis, in limiting the tissue damage associated with oxidative stress, and enhancing wound healing cannot be underestimated, but need to be evaluated further through multi-centered randomized controlled trials.